FACTORS IN THE INVESTMENT DECISIONS OF INVESTORS IN THE STOCK EXCHANGE OF THAILAND IN THE COVID-19 ERA - Thanyphaisan, Sirirak; Tangsattayacheep, Kraiwut; Thanyaphaisa, Siripa (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
The objective of this article was to study the factors that affect the investment decisions of investors on the stock exchange of Thailand that was inevitably affected by investment. The study revealed that the changing of paradigm understanding for the investment decision was important information for investors to assemble of Investment Strategy Formulation in the stock exchange appropriately and ultimately benefits. The factors considered in the investment decision include: 1) Personal factor of investors, 2) Knowledge factor of stock exchange investment, 3) Analysis factor to support investment in the Covid-19 Era, 4) Innovation and technology factor for investment. These factors in the investment decision of investors in the stock exchange of Thailand were the most important for consideration prudently of investors in order to occur the lowest risk because the risk in the Covid-19 Era for investment in the stock exchange was affected more than normal situation.